Do some financial product features negatively affect consumer decisions? A review of evidence - Pete Lunn; Féidhlim P. McGowan; Noel Howard (The Economic and Social Research Institute (ESRI), 2018)
This review identifies specific problems for consumers in credit, investment and insurance markets. It identifies multiple product features that are either poorly understood by many consumers or that generate systematic biases in their decisions.
Keywords: 330